Identificação de perdas por making-do e seus impactos em canteiros de obras goianos - Amaral, Tatiana Gondim; Elias, Karinny Vieira; Brandão, Camila Mariana; Braga, Pedro Boroatti (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The making-do stands out for representing a potential generator of other wastes, such as safety reduction, quality problems, productivity and rework. The paper seeks to analyze the production-related wastes by making-do in order to identify, through the categories of improvisation wastes, the impacts generated by them, from the perspective of the Goiás scenario. At the end of the analysis a matrix was applied for risk analysis of making-do wastes. Data were collected from three construction companies in the city of Goiânia. For data collection, data triangulation was performed through the results of interview analysis, direct non-participant observations, photographic records and document analysis. After data analysis, it is concluded that most improvisations are related to short term planning, logistics and projects. However, the most important impacts of these types of wastes are the need for rework and material waste. As a result, we highlight the importance of studying the wastes related to making-do, as it goes beyond the waste of materials, highlighting issues related to health and safety of the workforce and impacts on the production process as a whole.